Determinação multirresíduo de agrotóxicos em casca, polpa e tubérculo de batata empregando método QuEChERS e UHPLC-MS/MS - Amaral, Leonardo Rabello (2023)
Pesticides have been intensively used to control pests, weeds and diseases associated with various crops. Although these compounds protect crops, when the recommended doses for application are not respected, they can cause damage to health and the environment. Thus, this study aimed to develop and validate an analytical method for the multi-residue determination of pesticides in potatoes, as well as to evaluate the concentrations in the skin and pulp of the tuber using the original QuEChERS method and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). To clean the extracts, the dispersive solid phase extraction technique (d-SPE) was used using C18 as a sorbent. The method was validated for 82 compounds and the results showed that the method has a linear response in the range of 0.5 to 20 µg kg-1 . Accuracy and precision were evaluated at fortification levels 10, 25 and 50 µg kg-1 (n= 7), in repeatability and intermediate precision tests, showing recoveries between 70 and 120%, with RSD ≤ 20% for most levels and pesticides. The method presented quantification limits of 10 µg kg-1 for most pesticides. The proposed method was applied to commercial samples of potatoes and the occurrence of several pesticides was confirmed, including some prohibited for the potato crop. Subsequently, the distribution of pesticides in the peel and pulp was evaluated, indicating that some pesticides are concentrated in the peel and others in the pulp, depending on the physicochemical properties of the pesticides. The method was successfully applied to commercial samples and proved to be effective for routine analyses.